PENGARUH PERENDAMAN BENIH DALAM CaO DAN PEMUPUKAN P DAN K TERHADAP PENGENDALIAN KERACUNAN BESI PADA TANAMAN PADI DI LAHAN SULFAT MASAM POTENSIAL - Ani Susilawati; Izhar Khairullah (BERITA BIOLOGI, 2011)
Tidal land large enough sour sulfate and the potential for agricultural expansion. Obstacles encountered primarily stress iron poisoning. It has the potential to cause a decline in rice yield research aims to study the effect of the influence of seed treatment and fertilizer P and K to control iron toxicity in acidic sulfate potential land. This research was carried out in KP Belandean on MK 2007. Randomized block design with 3 replications. Rice varieties used were Batanghari, planted on plot measuring 4 mx 9 m with a spacing of 20 cm x 20 cm. Package combined treatment of seeds and fertilizer P and K: 1. (25-90-75), 2. (50-90-75), 3. (75-90-75), 4. (100-90-75), 5. (125-90-75), 6. (75-30-75), 7. (75-60-75), 8. (75-120-75), 9. (75-150-75), 10. (75-90-25), 11. (75-90-50), 12. (75-90-100), 13. (75-90-125), 14. (0-90-75), 15. (0-0-0) kg / ha% CaO-kg / ha P2O5-K2O. The result showed that by giving a dose of phosphate fertilizer 90 kg/ha P2O5 and potassium at a dose of 100-125 kg/ha K2O CaO combined with the provision of 75 % of the weight of the seed, is the combination to control iron poisoning.